Rapt in reading : recipes for literacy success - Wood, Beth.; Jorgensen, Glenda (Dalby, Qld : Heads Together, 1998)
Demystifying the reading process. About multiple intelligences. Multiple intelligences. Multiple intelligences. Test for young children. Verbal linguistic. Logical mathematical. Visual spatial. Body kinesthetic. Musical rhythmic. Interpersonal. Intrapersonal. My reading development chart.
Keywords: Education; Preschool Education; Preschool reading; Cognitive styles; Activity programs in education; Reading (Primary); Reading (Preschool); Cognitive styles -- Study and teaching; Activity programs in education